Michel and Mathurin: Finding Foucault in the Archives - Maynard, Steven (Archivaria)

(untitled) (Association of Canadian Archivists, 2025)
In this article, we follow Foucault into the archives. Foucault spent much of his working life reading and researching in libraries and archives, and yet he most often figures in the archival literature as the creator of the rarified concept of “the archive.” As a counterpoint, this article explores Foucault’s work in archives, his use of archives in his work, and the significance he attached to archival research. Ultimately, I contend that it is impossible to understand the abstract archive as concept without first grounding it in the experiential, epistemological, methodological, and political dimensions of finding Foucault in the archives.